Design and Characterization of a Bioinspired Polyvinyl Alcohol Matrix with Structural Foam-Wall Microarchitectures for Potential Tissue Engineering Applications - Ching-Cheng Huang (Polymers, 2022)
Traditional medical soft matrix used in a surgical treatment or in wound management was not good enough in both the structural support and interconnectivity to be applied in tissue engineering as a scaffold. Avian skeleton and feather rachises might be good reference objects to mimic in designing a scaffold material with good structural support and high interconnectivity because of its structural foam-wall microarchitectures and structural pneumaticity. In this study, a biomimetic airstream pore-foaming process was built up and the corresponding new medical soft matrix derived from polyvinyl alcohol matrix (PVAM) with air cavities inspired by avian skeleton and feather rachises was prepared. Furthermore, the resulting medical soft matrix and bovine Achilles tendon type I collagen could be employed to prepare a new collagen-containing composite matrix. Characterization, thermal stability and cell morphology of the bioinspired PVA matrix and the corresponding collagen-modified PVA composite matrix with open-cell foam-wall microarchitectures were studied for evaluation of potential tissue engineering applications. TGA, DTG, DSC, SEM and FTIR results of new bioinspired PVA matrix were employed to build up the effective system identification approach for biomimetic structure, stability, purity, and safety of target soft matrix. The bioinspired PVA matrix and the corresponding collagen-modified PVA composite matrix would be conductive to human hepatoblastoma HepG2 cell proliferation, migration, and expression which might serve as a promising liver cell culture carrier to be used in the biological artificial liver reactor.